Assessment of Nutritional Status in Patients with Cancer and Effectiveness of Oral Nutritional Supplements - Sanober Qadeer, Uzma Arshad, Ayesha Saddique, Zunaira Arshad, Samina Badar, Huzaifa Nazir Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2023)
Aims and Objectives; Malnutrition is prevalent among individuals with cancer and oral nutritional supplements can improve this issue. The aim of this study was to assess the nutritional status in patients with cancer and effectiveness of oral nutritional supplements. Material and Method; The present cross-sectional study was conducted in Multan Medical & Dental College, Multan form June 2023 to Sep 2023 after taking permission from the ethical board of the institute.“A total of 80 indivuals of different age groups (over 18 years) and both genders diagnosed with cancer who could take an oral diet and were receiving cancer therapy were included. Anthropometric measurements taken were physique, height, body mass index, weight for age (WFA), mid-upper-arm circumference, and triceps skinfold thickness (TSFT). Participants with malnutrition taken oral nutrition supplement from a registered dietitian. They were randomly assigned to receive protein- and energy-dense isocaloric or hypercaloric oral supplements and Resource junior. Individuals were followed up for 6 months, with nutritional valuations performed at the 3rd and 6th months. The nutritional status of the individuals was compared to anthropometric or biochemical parameters using parametric (T test, analysis of variance). The data was analyzed via SPSS 19. P-values ≤ 0.05 were considered statistically significant.”” Results: Overall 80 individuals with cancer were enrolled in this study. The mean age of the study participants was 29.1±7.9 years.“Preliminary anthropometric examinations demonstrated decreased incidences of malnutrition determined by weight or height in comparison to body mass index, weight for height, and arm anthropometry. Malnutrition was identified in 27 (33.7%) of those who met at least one of the following criteria: BMI below 5p, weight for height below 90 percent, triceps skinfold thickness or mid-upper-arm circumference lower than 5p, or over five percent weight loss prior to illness start. Participants with mid-upper-arm circumference & triceps skinfold thickness <5p showed no substantial reduction at evaluation or after 3 months. WFA went up significantly between the 1st, 3rd, and 6th months (P < 0.001). Significant rises were seen between the first & 6th months in weight for height, BMI, triceps skinfold thickness, & mid-upper-arm circumference. At the 3rd & 6th months, there was no significant difference in body mass index, weight for height, mid-upper-arm circumference, or triceps skinfold thickness among participants receiving isocaloric or hypercaloric supplements. There was a significant variation in mean blood pre-albumin levels between the first, third, and sixth months (P=0.05).” Conclusion: The current study concluded that malnutrion is very common in cancer patients and oral nutritional supplements can minimize the nutritional risk in these individuals Keywords: Assessment; Nutritional status; Cancer; Effectiveness